Key cases denial of maintenance to wife - Sharma, Jatin (Delhi LRC Publication, 2024)
(3z(BMaintenance Laws(3y (Bhave been enacted as a measure of social justice to provide recourse to dependent wife and children for their financial support, so as to prevent them from falling into destitution and vagrancy. There are different statutes providing for making an application for a grant of maintenance/interim maintenance, if any person having sufficient means neglects, or refuses to maintain his wife, children and parents. The different enactments provide an independent and distinct remedy framed with a specific object and purpose. Maintenance is awarded on the basis of the financial capacity of the husband and other relevant factors. Since it is the sacrosanct duty of the husband to provide financial support to the wife and minor children, the husband was required to earn money even by physical labour, if he is able-bodied, and could not avoid his obligation, except on any legally permissible ground mentioned in the statute. This book is a collection of judgments/orders of the Supreme Court of India and all High Courts where the maintenance was denied to the wife or the quantum of maintenance was reduced on different grounds. This book is not an attempt to advocate that wives are not entitled to maintenance but where evidence on record demonstrates legal permissible grounds for denial of maintenance to a wife, the courts should consider the same while disposing of the maintenance application/petition. It is to be borne in mind that the liberal interpretation of social welfare legislation is necessary to further the object of the legislation and not to dilute the same. The present book KEY CASES DENIAL OF MAINTENANCE TO WIFE covers maintenance cases in favour of the husband. The main approach and structure of the book have been retained in the Third Edition, however, with the addition of more case laws and citation of law journals this book has been completely revised.s
Keywords: Law; Maintance Law